Optimasi Produksi Enzim Lipase Dari Isolat Aspergillus oryzae - Seniwati Dali; Rauf Patong; Muhammad Noor Djalaluddin; Pirman AP (Hasanuddin University, 2010)
Production optimization of lipase enzyme from Aspergillus oryzae isolate on moldy copra has been conducted. Enzyme isolation is carried out after the fungi is activated and cultured on media containing peptone and olive oil at 370C in temperature and 7,0 in pH during 8 days. Production optimization of lipase enzyme is conducted by varying composition of production media, namely: peptone concentration and olive oil and optimal stirring speed. The study results showed that activity of the highest lipase enzyme is acquired on pepton concentration of 1 %, olive oil concentration of 3 % and the stirring speed is 150 rpm. Of concentration optimization of production media and stirring speed is acquired that there is an increasing activity of the lipase enzyme from 13.222 U/mL to 18888U/mL.